Byzantine and European Coins Found in Karacahisar Castle in the Historical Context - Hasan Yılmazyaşar; Zeliha Demirel Gökalp (Anadolu Araştırmaları)
Although Karacahisar Castle has been the subject of many publications due to its importance in the founding process of the Ottoman Principality, the information about the history of the castle is extremely limited. The main reason for this situation is that sources which provide information about the castle are almost non-existent. In this respect, the coins are among the important findings discovered in the archaeological excavations in the castle. The subject of this study is the Byzantine and European coins found in the archaeological studies carried out in Karacahisar Castle (Eskişehir) in two periods, between 2011 and 2014 and 2019 and 2021. During the Karacahisar excavations, seven Byzantine coins were found, as well as four Midilli Lordships, one Wallachian Principality coin, and two Nürnberg coins. In this study, catalog information was provided and evaluated under the historical context of the Byzantine, Lesbos-Gattilusio Lordship, and Wallachian Principality coins, as well as the Nürnberg tokens found in the Karacahisar Castle excavations. The Byzantine coins discovered indicate a Byzantine occupation of the castle, with interruptions from the 7th to the end of the 11th century. The role of Karacahisar in the historical process of Eskişehir, which also includes the castle, isamong the topics discussed in this study. European minted coins and tokens are the source of some important inferences in terms of medieval law, economics, and social history in the context of the coins being seized outside the country.